GAMBARAN JUMLAH TROMBOSIT TERHADAP PENDERITA TUBERKULOSIS SEBELUM DAN SESUDAH MENGKONSUMSI OBAT ANTI TUBERKOLOSIS PAKET (OAT) DI PUSKESMAS KECAMATAN KWANYAR KABUPATEN BANGKALAN - Riski Dwi Prameswari; Achmad Imam Wahyudi (Fakultas Ilmu Kesehatan Universitas Gresik, 2021)
Tuberculosis (TB) is a contagious infectious disease caused by mycobacterium tuberculosis. Germs aerobic rods and acid-resistant, it can be a pathogenic organism or saprofit. There are several mycobacterial pathogens, but only bovine and human strains of the human potogenik. The tubercle bacillus measuring 0.3 x 2 to 4 mm, this size is smaller than a red blood cell (price & wilson, 2005) .Peneliti using descriptive method, the observed characteristics are decreased platelet count in patients with tuberculosis before and after anti-tuberculosis drugs package OAT.Samples taken as an object of study as many as 15 samples were suffering from tuberculosis at the district health center. Kwanyar - Bangkalan, the results obtained before treatment platelet count is normal, whereas after treatment the average platelet count decreases. Dikarnakan there are two factors: decrease in endurance, and the platelet destruction occurs due to the adverse reaction to anti-tuberculosis drugs consumed OAT package so that platelets undergo lysis and decreased platelet count. The conclusion of the research results obtained are the effect of treatment on platelet count.